2017
DOI: 10.1177/0960327117701986
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid protects against arsenic trioxide–induced cardiotoxicity in rat

Abstract: Arsenic trioxide (AsO) is utilized for treating patients suffering from hematological malignancies particularly acute promyelocytic leukemia. Unfortunately, the extensive application of this chemotherapeutic agent has been limited due to its adverse effects such as cardiotoxicity. Ellagic acid, as a phenolic compound, has shown to exert antioxidant, anti-inflammatory, antifibrotic, and antiatherogenic properties. It is also capable of protecting against drug toxicity. In this study, we evaluated whether ellagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…Dose selection justifications varied between studies, but generally, in vivo doses were selected based on the literature [ 33 , 52 , 53 , 54 , 55 ]. For example, as a fraction of the lethal dose [ 56 ], or experimentally as the minimum dose that induced cardio-toxic effects [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dose selection justifications varied between studies, but generally, in vivo doses were selected based on the literature [ 33 , 52 , 53 , 54 , 55 ]. For example, as a fraction of the lethal dose [ 56 ], or experimentally as the minimum dose that induced cardio-toxic effects [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro arsenic doses were selected based on significant detrimental effects on cell viability and/or cell death and were further stratified by exposure duration ( Table 1 ). The studies presented in this review utilized arsenic trioxide (As 2 O 3 ) [ 32 , 45 , 53 , 54 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] or sodium arsenite (NaAsO 2 ) ( Figure 2 ) [ 49 , 55 , 56 , 67 , 68 , 69 , 70 , 71 ] at in vivo doses ranging from 0.8 mg/kg/day to 5 mg/kg/day administered intravenously or 2 mg/kg/day to 50 mg/kg/day administered orally for durations of 6 to 56 days. Experimental animals included Sprague Dawley rats [ 49 , 55 , 70 ], Wistar rats [ 59 , 67 ], BABL/c mice [ 72 ], APO E-/- mice [ 71 ], and guinea pigs [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates not only that diabetes mellitus-induced myocardial diastolic dysfunction is partly caused by reduction of sarco-endoplasmic reticulum Ca 2+ -ATP ase function, but also that it can be ameliorated by ellagic acid and other activators [213]. Ellagic acid exerts a cardioprotective effect against As 2 O 3 toxicity, a consequence of its antioxidant properties, which in this case enhance the endogenous antioxidant system [214]. It also protects against doxorubicin-induced cardiotoxicity in mice [215].…”
Section: Cardiovascular Effectsmentioning
confidence: 94%
“…EA prevented the serum cardiac markers, MDA and NO levels, while increased the levels of GSH content, and CAT, SOD and GPx activities in the heart of rats (Goudarzi et al, ). Additionally, EA (30 mg/kg, orally) mitigated the levels of serum cardiac markers, MDA and QTc prolongation, and enhanced the level of GPx activity following the arsenic trioxide‐induced cardio‐toxicity in rat (Hemmati et al, ). It is suggested that the cardioprotective effects of EA may be through its antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%